Mixed treatment comparison meta-analysis evaluating the relative efficacy of nucleos(t)ides for treatment of nucleos(t)ide-naive patients with chronic hepatitis B - Dakin, H; Fidler, C; Harper, C (Elsevier, 2011)
Background/aims Five nucleoside/nucleotide treatments are now available for chronic hepatitis B (CHB). This meta-analysis aimed to assess the relative efficacy of adefovir, entecavir, lamivudine, telbivudine, tenofovir disoproxil fumarate (TDF), and nucleos(t)ide combinations in the treatment of CHB.